Two new genera of Australian dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) with the description of six new species and transfer of six described species - Gunter, Nicole L.; Weir, Thomas A. (Zootaxa, 2017)
A complex of small scarabaeine dung beetles related to Lepanus Balthasar, 1966 (Coleoptera: Scarabaeidae: Scarabaeinae) is described, based on morphological and molecular characters. There are two new genera, six new species, and seven new combinations, including the transfer of one species to a pre-existing genus, as follows. Matthewsius Gunter & Weir new genus includes two new species, M. stricklandensis Gunter & Weir new species from central New South Wales, Australia and M. vanleeuweni Gunter & Weir new species from Pilbara region of Western Australia, Australia; two species formerly included within Aptenocanthon Matthews, 1974, M. rossi (Matthews, 1974) new combination and M. speewah (Storey & Monteith, 2000) new combination; and two species formerly included within Lepanus, M. illawarrensis (Matthews, 1974) new combination and M. penelopae (Matthews & Weir, 2002) new combination. Monteithocanthon Gunter & Weir new genus includes six species: Monteithocanthon elliotensis Gunter & Weir new species, Monteithocanthon koombooloomba Gunter & Weir new species, and Monteithocanthon paraarator Gunter & Weir new species from northern Queensland, Australia; Monteithocanthon peckorum Gunter & Weir new species from southwestern Western Australia; and two species formally included within Lepanus, Monteithocanthon arator (Matthews, 1974) new combination and Monteithocanthon glaber (Matthews, 1974) new combination. Sauvagesinella loftyensis (Matthews & Weir, 2002) new combination is transferred from Lepanus on the basis of genetic and morphological similarities.